Spirlins of the southern Black Sea basin, with the description of a new species (Teleostei: Leuciscidae) - Kaya, Cüneyt (Zootaxa, 2020)
Alburnoides turani, new species, from the Filyos River drainage is described and the distribution of the nine other Alburnoides species known from the southern Black Sea basin is revised. Alburnoides turani is distinguished by having a naked ventral keel, or the keel is covered with 1–3 scales between the posterior pelvic-fin base and the anus, an interorbital distance wider than the eye diameter and the snout length, 48–55 total lateral-line scales, 5–6 scale rows between the anal-fin origin and the lateral line, 13½–14½ branched anal-fin rays, and 41–42 total vertebrae.